Do Paramedics Have a Professional Obligation to Work During a Pandemic? A Qualitative Exploration of Community Member Expectations. (24th June 2020) - Anderson, Cameron; Pooley, Julie Ann; Mills, Brennen; Anderson, Emma; Smith, Erin C.
ABSTRACT: Objectives: Previous research has identified a lack of clarification regarding paramedic professional obligation to work. Understanding community expectations of paramedics will provide some clarity around this issue. The objective of this research was to explore the expectations of a sample of Australian community members regarding the professional obligation of paramedics to respond during pandemics. Methods: The authors used qualitative methods to gather Australian community member perspectives immediately before the onset of the coronavirus disease 2019 (COVID-19) pandemic. Focus groups were used for data collection, and a thematic analysis was conducted. Results: The findings revealed 9 key themes: context of obligation (normal operations versus crisis situation), hierarchy of obligation (individual versus organizational obligation), risk acceptability, acceptable occupational risk (it's part of the job), access to personal protective equipment, legal and ethical guidelines, education and training, safety, and acceptable limitations to obligation. The factors identified as being acceptable limitations to professional obligation are presented as further sub-themes: physical health, mental health, and competing personal obligations. Conclusions: The issue of professional obligation must be addressed by ambulance services as a matter of urgency, especially in light of the COVID-19 coronavirus pandemic. Further research is recommended to understand how community member expectations evolve during and after the COVID-19 coronavirus pandemic.